The effects of bleomycin, mitomycin C, and cytoskeletal-disrupting drugs on angiogenesis in vitro and haemangioma development in vivo - Pepper, Michael Sean (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.